Developing Stages for the Scientific Cues Concept in the Integrated Science-Tafseer Learning Model - Saputro, B.; Marjuni, K. M.; Kuswaya, A.; Saputra, H.; Fadly, W. (Jurnal Pendidikan IPA Indonesia, 2019)
This study aimed to determine the applicability of the scientific cues concept in developing the integrated science-Tafseer learning model. This was a Research & Development study. The subjects of this study were Tafseer lecturers and students of the Science Education Department of IAIN Salatiga. The data collection instruments were Likert scale questionnaires, discussion note formats, observation sheets, and pretest and integrated science-Tafseer post-test questions. The validity test results of scientific cues concept instruments showed that all items were valid (rxy> 0.3)and the instrument reliability was 0.73> 0.6 (reliable). The result findings of the needs assessment research on the scientific cues concept showed that the average (42) interpretation lecturers in Indonesia were = 3.62 with Ã¢â‚¬Å“Badly NeededÃ¢â‚¬Â category. Scientific cues of integrated science-Tafseer materials on the food theme in QS. Al-Baqarah 168, QS. Al-Maidah: 88, and QS. An-Nahl: 114 as follows: Ã™Æ’Ã™ÂÃ™â€žÃ™Ë† (eat) and Ã™â€¦Ã™ÂÃ™â€¦Ã™â€˜Ã˜Â§ (food). Scientific cues are the universal keywords of the integration of scientific facts of the QurÃ¢â‚¬â„¢an. The normality test result of the pretest and posttest data using Shapiro-Wilk obtained the significance of the pretest = 0.026 (p) <0.05 and the posttest = 0.00 (p) <0.05 (the data were not normally distributed). The effectiveness test of the scientific cues concept stages using the Wilcoxon test obtained a t-count of 4.790 with p = 0.000. Thus, the p-value was<0.05, meaning that the presentation of the concept of useful scientific cues can improve the learning outcomes and contribute to the stages of the concept of scientific cues in developing the integrated science-Tafseer learning model.